INOVASI PEMBELAJARAN ERA DIGITAL - Mega Nur Safira; Iswanto; Essha Kakesha Rajabiah (PT. Pustaka Andil Lestari, 2024)
In the world of education, learning innovation can be defined as developing and creating new innovations such as methods or technology used for learning with the aim of increasing efficiency, effectiveness and relevance to deal with changing times in the learning process. Teachers can innovate in various ways, including through the use of technology. various ways such as, the use of technology, curriculum changes, new teaching approaches and better evaluation methods. Learning innovation can be in the form of ideas, goods, or methods as something new in the world of education. In order for students not to be bored and interested in participating in learning activities, teachers must be creative and imaginative in providing teaching. The method used in this article is library research, by collecting data in the form of books, journals and articles related to learning innovation in the digital era. Examples of learning innovations that can be done in the digital era include e-learning, blended learning, cloud learning, hybrid learning, and flipped learning.